(untitled) - Petrie, Edward M. (New York, 2007)
The Handbook of Adhesives and Sealants, 2nd Edition is primarily written to assist all those who have a permanent or temporary interest in adhesives and sealants. For those new to the field, the Handbook will provide a fundamental knowledge base of materials and processes as well as reasons why they work and (more importantly) why they don’t work. To the more experienced reader, the breadth and thoroughness of the Handbook will provide a way to reduce time spent on trial and error development or on searching for the optimal recommended process. For the academic, the Handbook will connect the important theories regarding surface science, polymeric materials, and mechanics with practical products and applications of commercial significance.This edition includes major new sections on radiation curable adhesive, biological and naturally occurring adhesives, inorganic adhesives, role of bulk properties of the adhesive, non-destructive testing, and industrial application methods. A completely new chapter is devoted to adhesives used in various industries such as automobile, electrical / electronic, construction, packaging, aerospace, household do-it-yourself, and medical.
Keywords: Adhesives,Sealing compounds,Chất dính,Hợp chất bịt kín